Consequences of COVID-19 for Markets and Productive Systems - Khan, Syed Abdul Rehman (Brazilian Journal of Operations & Production Management, 2021)
In December 2019, the first case of COVID-19 was diagnosed in Wuhan city of China. The virus spread in several countries quickly and created pressure on the global supply chain and production systems. Undeniably, due to COVID-19, the world economy has been badly disrupted, which required a couple of years to restore. This special issue mainly uncovers the difficulties and challenges faced by firms during the COVID-19 outbreak. Also, the special issue covered the innovative approaches and applications of digital technologies to control the spread of COVID-19 and mitigating the harmful effects on economic activities through promoting teleworking and virtual business activities.